Addled by Technology - ORTEGA-VILLASEÑOR , Humberto; QUIÑONES TRUJILLO , Genaro (Utopía y Praxis Latinoamericana, 2024)
Unbridled individualism and the neoliberalism that has been its biggest booster in the last four decades has propagated the conviction, only recently challenged, that hypertechnology is the pinnacle of humankind’s aspirations and represents its future. This brief talk is a philosophical reflection about what it means to be human today, in an attempt to question the supposed infallibility of the technological project. The reflection draws on the cultural matrices of the original or autochthonous peoples of Mesoamerica, within the framework of the 19th-century philosopher Søren Kierkegaard’s thinking, which prefigured existentialism, and the technological scenario envisioned by the European philosopher Günther Anders (1902-1992). With these pieces we attempt to cobble together a modest body of ideas to contribute to the debate among thinkers and researchers from a wide range of disciplines (including ethnologists, historians, sociologists and psychologists) about the hypertechnological future of humanity. Our reflection aims to shed light on modern society’s blind, headlong rush into the technological project and the pressing need to recalibrate human existence at more natural scale.